2018
DOI: 10.1007/s42161-018-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

First report of leaf spot caused by Phytophthora capsici on chili pepper (Capsicum frutescens L.) in Pakistan

Abstract: A survey was conducted in chili and a leaf spot disease with approximately 46% incidence was observed in the field. Morphological characteristics of the isolates correspond to those reported for Phytophthora capsici. The resulting sequences of ITS and TEF1 gene had high similarity after BLAST analysis with those of P. capsici isolates. The pathogenicity of one isolate was tested by spraying the zoospore suspension and symptoms of leaf spots similar to those observed in the field developed on all the inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…A research study suggested that P. capsici isolates from pepper and pumpkin differ in virulence levels 32 . Morphologically identification confirmed the production of papillate sporangia on long pedicels, and Chlamydospores and these findings are supported by a study of 36 . According to 37 , Chamydospores production is not much common in Capsicum isolates but the formation of Chamydospores in P. capsici isolates depends on the cultural methods and the origin of the host 38 .…”
Section: Discussionsupporting
confidence: 75%
“…A research study suggested that P. capsici isolates from pepper and pumpkin differ in virulence levels 32 . Morphologically identification confirmed the production of papillate sporangia on long pedicels, and Chlamydospores and these findings are supported by a study of 36 . According to 37 , Chamydospores production is not much common in Capsicum isolates but the formation of Chamydospores in P. capsici isolates depends on the cultural methods and the origin of the host 38 .…”
Section: Discussionsupporting
confidence: 75%
“…(D) Heterozygosity levels in each gene family where total genes represent all annotated genes. 17 P. capsici isolates when characterized using pepper as a host (Nawaz et al, 2018). Our characterization study, based on root inoculation and a detached leaf assay, revealed the striking variation in the aggressiveness levels of three P. capsici isolates.…”
Section: Discussionmentioning
confidence: 88%
“…Different levels of aggressiveness among P. capsici isolates have been observed depending on the host and geographical variation (Granke et al, 2012;Nawaz et al, 2018;Siddique et al, 2019), however, the genomic comparison has not been performed. The broad distribution of P. capsici isolates with diverse aggressiveness levels impacts the breeding and deployment of resistant varieties of host crops (Foster and Hausbeck, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chilli peppers have been cultivated worldwide and are one of the essential vegetable fruits in some regions (FAOSTAT, 2016). Significant constraints to pepper fruit production include pests and diseases (Barchenger et al, 2018; Duarte et al, 2015; Nawaz et al, 2018; Saxena et al, 2016). Much progress has been made on increasing knowledge on function of various defence genes in pepper (Jaiswal et al, 2019; Zhang et al, 2019; Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%